A New Way for Effective Reducing Brake Temperature and Noise of Brake Pad - JIN Jiansheng; YANG Yang; NIU Lianjie; FAN Mengzhen; ZHANG Dingquan (机车电传动)
With the theoretical analysis of friction brake temperature and brake noise, and adjusting formulation and process, a new type of microporous composite brake pad was developed successfully, which had a microporous structure to effectively reduce friction heat, so that it could reduce brake temperature, decrease hot spots, cracks and spalls of brake disc, reduce brake noise and brake wear, as well as reduce the emission of dust, which is more environment friendly.